Developing the script “degenerate primer 111” to enhance the coverage of universal primers for the small subunit rRNA gene on target microorganisms - Qin, Zhihui; Xu, Xin; Xu, Fengjun; Zhang, Yao; Su, Peng; Shen, Chaofeng (Frontiers in Microbiology, 2024)
Amplifying small subunit (SSU) rRNA genes with universal primers in assessing microbial populations diversity, but target microorganisms are sometimes omitted due to inadequate primer coverage. Adding degenerate bases to primers can help, but existing methods are complex and time-consuming. This study introduces a userfriendly tool called "Degenerate primer 111" for adding degenerate bases to existing universal primers. By aligning one universal primer with one uncovered target microorganism's SSU rRNA gene, this tool iteratively generates a new primer, maximizing coverage for the target microorganisms. The tool was used to modify eight pairs of universal primers (515F Parada-806R Apprill, S-D-Bact-0341-b-S-17/S-D-Bact-0785-a-A-21, OP_F114-KP_R013, 27F-1492R, 341F-806R, OP_F066-KP_R013, 515F Parada-926R Quince, 616*F-1132R), and generated 29 new universal primers with increased coverage of specific target microorganisms without increasing coverage of non-target microorganisms. To verify the effectiveness of the improved primers, one set of original and improved primers (BA-515F-806R and BA-515F-806R-M1) was used to amplify DNA from the same sample, and high-throughput sequencing of the amplicons confirmed that the improved primers detected more microbial species compared to the original primers. Future researchers can use this tool to develop more personalized primers to meet their diverse microorganism detection needs.